Improvement of PolSAR decomposition scattering powers using a relative decorrelation measure. Issue 4 (3rd April 2017) - Ratha, D.; Surendar, M.; Bhattacharya, A.
ABSTRACT: In this letter, a methodology is proposed to improve the scattering powers obtained from model-based decomposition using Polarimetric Synthetic Aperture Radar (PolSAR) data. The novelty of this approach lies in utilizing the intrinsic information in the off-diagonal elements of the 3 × 3 coherency matrixT represented in the form of complex correlation coefficients. Two complex correlation coefficients are computed between co-polarization and cross-polarization components of the Pauli scattering vector. The difference between modulus of complex correlation coefficients corresponding to (i.e., the degree of polarization (DOP) optimized coherency matrix), andT (original) matrices is obtained. Then a suitable scaling is performed using fractions i.e., obtained from the diagonal elements of the matrix. Thereafter, these new quantities are used in modifying the Yamaguchi 4-component scattering powers obtained from . To corroborate the fact that these quantities have physical relevance, a quantitative analysis of these for the L-band AIRSAR San Francisco and the L-band Kyoto images is illustrated. Finally, the scattering powers obtained from the proposed methodology are compared with the corresponding powers obtained from the Yamaguchi et. al ., 4-component decomposition and the Yamaguchi et. al ., 4-component Rotated decomposition for the same data sets. The proportion of negative power pixels is also computed. The results show an improvement on all these attributes by using the proposed methodology.